Deep and Superficial Cases in Russian Beitraege zur Kasusgrammatik der slawischen Sprachen 2 - Kilby, David A. (Specimina philologiae Slavicae, 1977)
The purpose of the present study is to search for some theoretically satisfying way of describing the case system of Russian. The fundamental justification of this study that the problem of superficial cases, in spite of being one of the most researched areas of language, has not been given a satisfactory solution - so much so that even the problem of what to look for in an analysis of cases is completely open.